Protecting the Poor in a Crisis - and Beyond - Ravallion, Martin (World Bank, Washington, DC, 2012)
A well-designed public safety net can provide aid to the poor in times of need. Two basic principles should guide safety net policies: 1) Safety nets should efficiently insure the poor; to do so they must respond flexibly to the needs of the poor. 2) Safety nets should be an intrinsic part of longer-term development goals. This Note offers basic guidelines for designing an effective safety net, taking into account its potential role during normal times as well as crises.